Pelizaeus–Merzbacher disease: Cellular pathogenesis and pharmacologic therapy. Issue 5 (October 2014) - Torii, Tomohiro; Miyamoto, Yuki; Yamauchi, Junji; Tanoue, Akito
Abstract Pelizaeus–Merzbacher disease (PMD) is a rare leukodystrophy that causes severe dysmyelination in the central nervous system in infancy and early childhood. Many previous studies showed that various proteolipid protein 1 (plp1) mutations, including duplications, point mutations, and deletions, lead to oligodendrocyte dysfunction in patients with PMD. PMD onset and clinical severity range widely, depending on the type of plp1 mutation. Patients with PMD exhibit a delayed mental and physical development phenotype, but specific pharmacological therapy and clinical treatment for PMD are not yet well established. This review describes PMD pathology and establishment of new clinical treatment for PMD. These findings support the development of a new therapy for PMD and these treatments may improve the quality of life in patients with PMD.